The mites (Acari) associated with bark beetles in the Koli national park in Finland - Ritva Penttinen; Heli Viiri; John C Moser (Les Amis d'Acarologia, 2022)
Thirty-three taxa associated with Ips typographus were identified, of which fifteen species were phoretic.
The most abundant species were Insectolaelaps quadrisetus (Mesostigmata), Siculobata lentonycha (Oribata), Diapterobates
humeralis (Oribata), Ereynetes propescutulis (Prostigmata), Aetiophenax ipidarius (Prostigmata), and an unidentified species
of Nanacarus (Astigmata). Eight species – I. quadrisetus, Proctolaelaps fiseri, Trichouropoda polytricha, Mexecheles virginiensis,
A. ipidarius, E. propescutulis, Bonomoia pini, and Boletoglyphus boletophagi - and four genera - Nanacarus, Elattoma, Schwiebia,
and Parawinterschmidtia – were new taxa in Finland.